Blood Glutamate Scavenging With Pyruvate as a Novel Preventative and Therapeutic Approach for Depressive-Like Behavior Following Traumatic Brain Injury in a Rat Model - Frank, Dmitry; Gruenbaum, Benjamin F.; Shelef, Ilan; Zvenigorodsky, Vladislav; Severynovska, Olena; Gal, Ron; Dubilet, Michael; Zlotnik, Alexander; Kofman, Ora; Boyko, Matthew (Frontiers in Neuroscience, 2022)
Depression is a common and serious complication following traumatic brain injury (TBI). Both depression and TBI have independently been associated with pathologically elevated extracellular brain glutamate levels. In the setting of TBI, blood glutamate scavenging with pyruvate has been widely shown as an effective method to provide neuroprotection by reducing blood glutamate and subsequent brain glutamate levels. Here we evaluate pyruvate as a novel approach in the treatment and prevention of post-TBI depression-like behavior in a rat model. Rats were divided into five groups: 1) sham-operated control with pyruvate, 2) sham-operated control with placebo, 3) post-TBI with placebo, 4) post-TBI given preventative pyruvate, and 5) post-TBI treated with pyruvate. These groups had an equal number of females and males. Rats were assessed for depressive-like behavior, neurological status, and glutamate levels in the blood and brain. Post-TBI neurological deficits with concurrent elevations in glutamate levels were demonstrated, with peak glutamate levels 24 h after TBI. Following TBI, the administration of either prophylactic or therapeutic pyruvate led to reduced glutamate levels, improved neurologic recovery, and improved depressive-like behavior. Glutamate scavenging with pyruvate may be an effective prophylactic and therapeutic option for post-TBI depression by reducing associated elevations in brain glutamate levels.